Case Report: Treatment of Oral Lichen Planus With a Focus on Psychological Methods - Song, Xiuli; Wu, Xueqi; Wang, Chunye; Sun, Shuguang; Zhang, Xiangyang (Frontiers in Psychiatry, 2021)
Oral lichen planus (OLP) is one of the most common chronic diseases; however, its etiology remains unknown. More and more studies have revealed that emotional instability is one of the risk factors for the onset and expansion of OLP, especially in patients suffering from depressive disorder, anxiety disorder, and acute stress. In this case report, we had a 32-year-old female patient with OLP who had no obvious response to conventional OLP drugs. Then we switched to a combination of psychotropic medications and psychotherapies. By regulating mood through drugs and psychological counseling, the oral disease of patient was alleviated. Our case shows that clinicians should consider the mental problems of OLP patients. It also emphasizes the importance of medications and psychological counseling in the treatment of somatic diseases.